2018
DOI: 10.2196/games.8979
|View full text |Cite
|
Sign up to set email alerts
|

The Praise and Price of Pokémon GO: A Qualitative Study of Children’s and Parents’ Experiences

Abstract: BackgroundPhysical activity has multiple health benefits; however, the majority of children around the world do not attain the recommended levels of daily physical activity. Research has shown that the game Poké mon GO has increased the amount of physical activity of players and that the game has the potential to reach populations that traditionally have low levels of physical activity. Therefore, there is a need to understand which game components can promote initial and sustained physical activity. By using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 20 publications
4
62
0
Order By: Relevance
“…Harris and Crone (2018) conducted focus groups with 28 adult Beat the Street players post-intervention and found there were 4 alternative themes pertinent to the ways participants took part in the game, these were game reinvention, altering the game to suit individual ideas and preferences (such as role playing); social influence, taking part in an activity with or for family, friends and/or colleagues; exploration, which involved discovering the local area, finding new routes and greenspaces and orienteering to ‘collect’ ‘Beat Boxes’ and collective extrinsic reward, where players were motived by collective, rather than individual gain (for example, money for charity). Elsewhere, Lindqvist et al (2018) with a study including 8 families, identified 2 themes pertaining to engagement with Pokémon GO. Firstly, the participant's recognised the positive benefits associated with gameplay and described the game as increasing outdoor physical activity and therefore parents and children encouraged each other to player along.…”
Section: Discussionmentioning
confidence: 99%
“…Harris and Crone (2018) conducted focus groups with 28 adult Beat the Street players post-intervention and found there were 4 alternative themes pertinent to the ways participants took part in the game, these were game reinvention, altering the game to suit individual ideas and preferences (such as role playing); social influence, taking part in an activity with or for family, friends and/or colleagues; exploration, which involved discovering the local area, finding new routes and greenspaces and orienteering to ‘collect’ ‘Beat Boxes’ and collective extrinsic reward, where players were motived by collective, rather than individual gain (for example, money for charity). Elsewhere, Lindqvist et al (2018) with a study including 8 families, identified 2 themes pertaining to engagement with Pokémon GO. Firstly, the participant's recognised the positive benefits associated with gameplay and described the game as increasing outdoor physical activity and therefore parents and children encouraged each other to player along.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using self-reported data indicated that players spent more time outside and performed more physical exercise because of Pokémon GO [ 23 - 26 ]. Other research included studies on Pokémon GO players’ motivations [ 27 , 28 ], experiences while playing Pokémon GO [ 29 ], and potential adverse effects associated with playing Pokémon GO [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the technology used, the variety of games and materials in the program came to the fore as a powerful factor in ensuring the integrity of the program. Studies on this topic indicate that various physical activities and games for school-age children also diversify targets and enable children to become more active (Lindqvist, Castelli, Hallberg, and Rutberg, 2018;Prichard, 2012;Schoenau-Fog, 2011).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%